2011
DOI: 10.1016/j.bbr.2011.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the effects of ethanol pre-exposure during adolescence on ethanol-induced conditioned taste aversion in adult rats

Abstract: Alcohol use, which typically begins during adolescence and differs between males and females, is influenced by both the rewarding and aversive properties of the drug. One way adolescent alcohol use may modulate later consumption is by reducing alcohol s aversive properties. Here, we used a conditioned taste aversion (CTA) paradigm to determine if pre-exposure to alcohol (ethanol) during adolescence would attenuate ethanol-induced CTA assessed in adulthood in a sex-dependent manner. Male and female Long-Evans r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
43
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 71 publications
11
43
2
Order By: Relevance
“…After three pairings of the CSa and 1.5 g/kg ethanol, males were consuming 94.1% less CSa than they were at baseline; females were consuming 68.9% less (see Table 1). These results are consistent with those obtained by several other research groups (Caihol and Mormede, 2002;Morales et al, 2014;Schramm-Sapyta et al, 2014;Sherrill et al, 2011a). In fact, a relative sensitivity of males as compared to females with this preparation is generally reported, although the strength of the sex difference varies across studies and is dependent upon a number of factors (see Busse et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…After three pairings of the CSa and 1.5 g/kg ethanol, males were consuming 94.1% less CSa than they were at baseline; females were consuming 68.9% less (see Table 1). These results are consistent with those obtained by several other research groups (Caihol and Mormede, 2002;Morales et al, 2014;Schramm-Sapyta et al, 2014;Sherrill et al, 2011a). In fact, a relative sensitivity of males as compared to females with this preparation is generally reported, although the strength of the sex difference varies across studies and is dependent upon a number of factors (see Busse et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…The results of our experiments could indicate, on the one hand, that the enhanced sensitivity of male rats to ethanol-induced aversion (experiment 1), may contribute to their reduced voluntary ethanol intake behavior (non-experienced males of experiment 2; Cacace et al, 2011;Doremus et al, 2005;Sherrill et al, 2011aSherrill et al, , 2011bTruxell et al, 2007;Vetter-O'Hagen et al, 2009;Vetter-O'Hagen and Spear, 2011). Consistent with this notion, previous studies have demonstrated an inverse relationship between ethanol self-administration and ethanol-induced FAL, though this may be strain dependent (reviewed in Sherrill et al, 2011a).…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations